A Review of Yemeni Endemic Aloes - Al-Wajih, Asmaa; El-Shaibany, Amina Mohammed; El-Aasser, Mahmoud Mohammed (PSM Microbiology, 2022)
For thousands of years, plants have been an important source of medicine in pharmaceutical biology. As per WHO, 80% of the population today relies on traditional medicine. The genus Aloe, family Asphodelaceae (Xanthorrhoeaceae), is a collection of flowering succulents consisting of over 500 known species, including Aloe vera, Aloe barbadensis, Aloe ferox, Aloe chinensis, Aloe indica, Aloe perryi, etc. A. perryi, also known as Perry’s aloe, is endemic to the island of Socotra in Yemen. Its natural habitat is the dry rocky areas. Chemically, Aloe possesses various pharmacologically important compounds, such as essential oils, alkaloids, amino acids, anthraquinone glycosides, glycoproteins, vitamins, minerals, and lectins.